The Use of Corpus Data To Assess the Functional Potential Of the Grammeme (on the basis of the Ukrainian vocative case) - Kobchenko, Natalia (Theoria et Historia Scientiarum, 2025)
It is known that changes on the grammatical level of the language system occur less frequently and more slowly than at the lexical level, and therefore it is difficult to notice and record them from a synchronic perspective. Observations of certain grammar shifts in communication of some professional or territorial communities do not allow us to fully assess the grammar trend. Thus, this study aims to apply corpus data (in particular General Regionally Annotated Corpus of the Ukrainian Language (GRAC) to assess the functional competition between the vocative and nominative in expressing address to the recipient of the speech. The paper proposes a new methodology to assess the functional potential of the grammar form. It is based on the thesis of the correlation between the functional strength of a grammar form and its ability to extend to newly-derived words. A group of feminine personal nouns that came into use in recent decades (not recorded in the Ukrainian Language Vocabulary in 11 volumes) served as lexical data for testing this methodology. The results of analysis of the case forms that are common for feminine personal nouns in the addressee position lead to the following conclusions: 1) refuting the statement about the expansion of the nominative in the modern Ukrainian language due to it displacing the vocative; 2) introducing feminine personal nouns into the address domain of the vocative.